Pendidikan Karakter pada Pembelajaran Agama Islam untuk Anak Berkebutuhan Khusus Autism Spectrum Disorder (ASD) di SLB Mitra Ananda Karanganyar - Raharja, Sigit (Indonesian Journal of Elementary Education and Teaching Innovation, 2025)
Character education is a basic thing in education that will be achieved for every individual, including students with Autism Spectrum Disorder (ASD). This study aims to explore effective ways to internalize character education in Islamic religious education learning for children with special needs Autism Spectrum Disorder (ASD) and describe the learning media used by teachers and what character education values are achieved in Islamic religious education learning for children with special needs Autism Spectrum Disorder (ASD) at SLB Mitra Ananda. The type of research that the researcher conducted used a descriptive qualitative method. The data analysis used three activity paths, namely data reduction, data display, and drawing conclusions. This research was conducted at SLB Mitra Ananda Karanganyar. Data collection techniques using observation, interviews, and documentation. The subjects of the study were approximately 50 Autism Spectrum Disorder (ASD) students and the informants were Islamic religious education teachers, vice principals for curriculum, and principals. From the results of data analysis, it was concluded that character education in Islamic religious education learning for Autism Spectrum Disorder (ASD) students was implemented through various activities including through activities to get used to praying in congregation, learning to memorize prayers and short letters, learning to recite the Koran. These habits can provide reinforcement for the formation of children's character education values. Then in delivering the material, the teacher uses visual learning media by utilizing concrete illustrated and audio-visual learning media by prioritizing the characteristics and needs of each student with special needs Autism Spectrum Disorder (ASD). The results of this study indicate the importance of providing reinforcement of strategic steps in Islamic religious education learning that can be achieved especially in developing character education values for students with special needs Autism Spectrum Disorder (ASD).Keyword: Religious Character Education, Islamic Religious Education, Autism Spectrum Disorder (ASD)